2020
DOI: 10.3390/ijerph17176108
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Study of Children’s Nutritional Status and Identification of Community-Level Nursing Diagnoses in a School Community in Africa

Abstract: Effectively responding to children’s nutritional status and eating behaviors in Mozambique requires a community-based care approach grounded in sound nursing research that is evidence-based. The Community Assessment, Intervention, and Empowerment Model (MAIEC) is a nursing theoretical model that is based upon clinical decision-making for community health nurses using communities as a unit of care. We used the MAIEC to identify a community-based nursing diagnosis to address children’s nutritional status and eat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…In addition, these community nurses visit families, check the health condition of the children, provide health education and offer telephone consultations [10]. A previous study suggested that the nutritional status of children in Africa could be assessed promptly and accurately by community-based nursing [11]. National policies have begun to intervene in the prevention of unintentional injuries [12].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these community nurses visit families, check the health condition of the children, provide health education and offer telephone consultations [10]. A previous study suggested that the nutritional status of children in Africa could be assessed promptly and accurately by community-based nursing [11]. National policies have begun to intervene in the prevention of unintentional injuries [12].…”
Section: Discussionmentioning
confidence: 99%
“…Foram identificados diagnóstico de enfermagem e critérios diagnósticos para estado nutricional e manejo comunitário. A necessidade de intervir com uma abordagem multidisciplinar de saúde pública é imperativa, tendo a comunidade escolar como unidade de cuidado (MELO, 2020).…”
Section: )unclassified
“…This nursing model offers an integrative vision of stakeholders and local structures and provides a clinical decision matrix to guide nurses’ decision-making. Conceptual approach [ 40 ] and empirical approaches through a cross-sectional quantitative study (developed in a community of schools in Africa to address children’s nutritional status and eating behaviors - [ 41 ]) and focus groups (with four Portuguese primary healthcare structures to improve the epidemiological monitoring of nursing diagnoses – [ 42 ]). Community empowerment is approached as a dynamic process articulated around three components: - Community leadership related to the community’s knowledge, beliefs, behaviors, and wishes in the context of the problem addressed; - Community participation related to communication, partnerships, and the existence of organizational structures; - Community process related to community coping or experiences with the problem addressed.…”
Section: Introductionmentioning
confidence: 99%